2023
DOI: 10.1177/17446295231184116
|View full text |Cite
|
Sign up to set email alerts
|

Challenging behaviors in adults with autism spectrum disorder and intellectual disability: A differential analysis from a transdiagnostic approach

Abstract: This study aimed at analyzing the differences in challenging behaviors between adults with intellectual disability and ASD and those who only had intellectual disability, as well as to explore associations between transdiagnostic and clinical variables to these differences. Therapists and educators of 163 adults with intellectual disability (83 with additional ASD diagnosis) completed the test battery. Mean difference analysis and univariate analyses of covariance were performed to determine the impact of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…; DSM-5; American Psychiatric Association, 2022) description of autism, there is some evidence that it is quite common in autistic children (Nicholls et al, 2020). It may be especially common among autistic people with co-occurring intellectual disability, who appear to have greater incidences of problem behavior than those with autism alone or intellectual disability alone (Álvarez-Couto et al, 2023;Murphy et al, 2009). In this study, we examine intervention research designed for autistic youth that addresses problem behavior, to understand: the characteristics of participants included in this research, how problem behavior is conceptualized and identified, and the strategies used to address it.…”
mentioning
confidence: 99%
“…; DSM-5; American Psychiatric Association, 2022) description of autism, there is some evidence that it is quite common in autistic children (Nicholls et al, 2020). It may be especially common among autistic people with co-occurring intellectual disability, who appear to have greater incidences of problem behavior than those with autism alone or intellectual disability alone (Álvarez-Couto et al, 2023;Murphy et al, 2009). In this study, we examine intervention research designed for autistic youth that addresses problem behavior, to understand: the characteristics of participants included in this research, how problem behavior is conceptualized and identified, and the strategies used to address it.…”
mentioning
confidence: 99%